Penggunaan Bejana Emas dan Perak dalam Perspektif Hadis - Ghina Mutmainnah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about gold and silver vessels. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about gold and silver vessels in Muslim history No. 3849. The results and discussion of this study indicate that the status of quality hadith is shahih that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Muslim No. 3849 is relevant to be used as knowledge and evidence to be used as a reference regarding the prohibition of the use of gold and silver vessels.